STUDI LITERATUR KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR SELAMA PEMBELAJARAN DARING - Bagus Putra Sanjaya (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
The rapid increase in the number of cases of people exposed to Covid-19 has led the government to implement various policies. In the field of education, the government provides a policy for implementing online learning or distance learning to support the continuity of the education process during the Covid-19 pandemic. However, the implementation of this policy is certainly not easily accepted by various parties involved in it, especially students at the elementary school level. Therefore, this study aims to determine the development of learning independence for elementary school students while participating in online learning during the Covid-19 pandemic. This article is compiled by conducting a literature study of scientific articles, books, and various other reading sources that are relevant to online learning and independent learning of elementary school students. The results of the study show that the implementation of student-centered learning online encourages students to always participate actively in every learning activity and develop their learning independence. Even though during online learning, students tend to feel bored, disobey when taught by parents, and do not yet have the initiative of their own to learn. However, online learning has also succeeded in building students' visual learning styles well, improving literacy, increasing self-confidence and a sense of responsibility for primary school students. Thus, the application of online learning is considered effective in breaking the chain of spreading Covid-19 and creating independent learning for elementary school students.